Новый вид цикадки рода афродес - Aphrodes Curt. (Auchenorrhyncha, Cicadellidae) - с Кавказа - Логвиненко, В.Н. (Вестник зоологии, 1967)
Aphrodes vallicolis Logvinenko, sp. n.— a new representative of the Cicadellidae family is described according to the series of leaf-hoppers, collected by the author in Klukhorskaya valley (the Caucasus, Teberdinsky reservation). A new species is chracterized by the soft greyish brown colour of integuments with two slightly expressed light-coloured bands of the upper wings in males. The clearest distinctions of this species from all the similar species are observed in the structure of genital organs of the males. Penis is strongly laterally flattened, has two pairs of appendices. The apical pair which is arranged on the dorsal side is twice as long as the low pair, which is ar-ranged on the ventral side. Gonopor is on the dorsal side of penis on the level of the bases of apical appendices.